Emma all stirred up! - Simon, Coco (Simon, Coco. Cupcake diaries, 2012)
"Emma is not thrilled with always needing to rearrange her schedule to babysit her younger brother, Jake, after school. But it's summer, and Emma is free--or so she thinks. Emma's parents have broken the news that really threatens to push Emma over the edge: Emma and Jake are going to the same day camp together. And Emma will have to babysit Jake on the bus. Every day. Can't Emma catch a break?"--Publisher.